Examination of Opinions of the Senior Health Managers Working in Private Hospitals on Health Technology Assessment - Mehmet Akif Erişen; Fatma Özlem Yılmaz (Association of Nurse Managers, 2020)
INTRODUCTION: In this study, it was aimed to evaluate the views and opinions of the health administrators, who are working in the private hospitals in Konya province centre about health technology assessment and applications. METHODS: Qualitative research methods have been used in research, and phenomologic method is preferred. The research was conducted using face-to-face interviews with health administrators working in private hospitals serving in the centre of Konya and accepting to participate in the research. A semi-structured interview form was used as a data collection tool in the survey. RESULTS: As a result of the analysis, sub-themes were created under the headings of health technologies, health technology assessment, health technology assessment applications in Turkey, health technology assessment approach of private hospitals, establishment of health technology assessment department, health technology assessment applications of the respondents' hospitals and future position of health technology assessment. And the findings under the created themes are interpreted. DISCUSSION AND CONCLUSION: The managers had various information about health technology assessment applications however it was limited. In this respect, it would be beneficial to provide a general education about health technology assessment in order to increase awareness and application of health technology assessment practices.